Comparative Analysis of the Health Level of Islamic Banks and Conventional Banks in Indonesia Before (2017-2019) and During Covid 19 (2020-2022) Using RGEC Method - Miptahudin, Iip; Nur Rizqi Rhommadhonni, Vania; Prabandari, Fitriana; Gemma Nurrahman, Ahmad (Islamicate Institute, 2023)
This research aims to analyze the differences in the health of Sharia Banks and Conventional Banks in Indonesia before and during Covid-19. The research method used was quantitative descriptive using the RGEC method, data analysis using the Normality Test, and the Wilcoxon Signed Difference Test. The sampling technique used was a purposive sampling technique with the criteria of Islamic banks and conventional banks having core capital of less than 3 trillion. The samples obtained were 4 Sharia Commercial Banks and 7 Conventional Commercial Banks. The data comes from the bank's quarterly financial reports and GCG reports for the 2017-2019 (Before Covid-19) and 2020-2022 (During Covid-19) periods. The overall level of bank health using RGEC analysis shows that Sharia Commercial Banks are in a